Evaluating of the Protective Effect of Vitamin E Against the Histological and Biochemical Effects of Methamphetamine on the Rat Liver - Anhar Rabeea Hussein (American Journal of Biology and Natural Sciences, 2026)
Methamphetamine is a powerful central nervous system stimulant belonging to the amphetamine class, it increases the release of dopamine and norepinephrine, causing feelings of energy and euphoria. It is considered a highly addictive substance, and its use is associated with psychiatric and neurological disorders, as well as cardiovascular and immune system diseases. Chronic use can also lead to changes in brain function that affect memory and behavior, making it a significant health and social problem. The study aims to evaluate the protective effect of vitamin E against the toxic effects of methamphetamine on the histological structure of the liver in male rats and on liver function through the analysis of liver enzymes (ALT, AST, ALP) over different time periods. This study included 28 male Sprague-Dawley rats, divided into 7 groups of 4 animals each. The first group served as the control group and was fed a standard diet and water throughout the experiment. The second group was administered methamphetamine at a concentration of 0.1 mg/kg for 15 days, in addition to water and food. The third group was administered methamphetamine at a concentration of 0.1 mg/kg for 30 days, The fourth group was administered vitamin E at a concentration of 0.1 mg in two drops for 15 days; the fifth group was administered vitamin E at a concentration of 0.1 mg in two drops for 30 days; the sixth group was administered methamphetamine at a concentration of 0.1 mg/ kg along with vitamin E as a protective agent at a concentration of 0.1 mL for 15 days, and the seventh group was administered methamphetamine at a concentration of 0.1 mg/kg along with vitamin E at a concentration of 0.1 mL for 30 days, Microscopic examination of the tissue sections revealed numerous histological changes in the liver, including cellular necrosis and degeneration accompanied by hepatocyte hypertrophy, with some nuclei appearing enlarged and surrounded by cytoplasmic vacuoles, as well as hemorrhage and significant infiltration of inflammatory cells, as well as detachment of endothelial cells from the central vein lining and an increase in the number and size of Kupffer cells. Biochemical test results for blood samples measuring liver function showed abnormalities in ALT and AST levels, leading to a decrease that persisted as the duration of treatment increased. This decrease in activity, despite cellular swelling, may be attributed to the depletion of enzymatic reserves within hepatocytes or to the inhibition of protein synthesis resulting from the severe oxidative stress caused by the drug; However, the alkaline phosphatase (ALP) enzyme showed a sharp increase with prolonged treatment duration, as elevated ALP levels are a significant indicator of obstruction or irritation of the bile ducts resulting from inflammation, This study concludes that the use of methamphetamine for varying periods of time causes liver damage that becomes more severe over time, progressing from minor structural abnormalities (15 days) to cellular necrosis, complete tissue death, and blood clots (30 days). Vitamin E, on the other hand, provides good protection during the short-term period (15 days) by improving liver function and reducing enzyme levels (AST, ALT); however, this efficacy diminishes in the face of chronic toxicity over the long term.